RASIO KINERJA KEUANGAN DAERAH DAN PEMBIAYAAN INFRASTRUKTUR DI KABUPATEN BONDOWOSO - KRISTIAN BUDITIAWAN; Eko Budi Santoso (Inovasi, 2022)
In the era of decentralization, each autonomous region in Indonesia has the capacity and ability to determine the direction of development goals in accordance with the conditions of their respective regions, including managing regional financial resources to achieve national development goals in their regions. Fiscal decentralization is intended to balance the pace of development between regions so that there is no longer a dichotomy of developed and underdeveloped regions because each region has the opportunity to independently finance development in its region according to its regional potential. Law Number 23 of 2014 concerning Regional Government opens wide opportunities for regions to run their government by utilizing available resources in their regions and relying a little on central government assistance. For this reason, the Regional Government tries to use its regional revenue sources as well as possible to finance the ongoing government process. Financial performance ratio analysis is an attempt to assess regional financial performance in order to fulfill the elements of accountability for good governance. This study will discuss the ratio of regional financial performance associated with the ability of the region to finance development in Bondowoso Regency. The analytical method used is an analysis of regional financial performance which includes aspects of the effectiveness ratio, efficiency ratio, independence ratio, activity ratio, and growth ratio. Bondowoso Regency's financial performance during the 2016-2020 period can be said to be overall good in terms of effectiveness ratios and efficiency ratios. The independence ratio still shows the proportion of transfer receipts from the provincial/central government is still greater than the original regional income. The activity ratio illustrates that revenue is still more used to finance operational expenditures compared to capital expenditures (providing infrastructure). Infrastructure financing can use funds sourced from General Allocation Funds, Special Allocation Funds, Regional Loans, government collaboration with business entities, and funds sourced from CSR companies in Bondowoso Regency.